Research on the coordinated development of resource-based cities in Sichuan Province: from the perspective of industrial structure and ecological environment - Liu, Kexin; Fan, Xinyue; Yang, Xiaoyi; Zhang, Yongqiang; Feng, Tingting (Frontiers in Environmental Science, 2023)
During their journey of developing, resource-based cities gradually deplete the resources on which they rely for survival. Scientific and reasonable research on the industrial and ecological aspects of resource-based cities is conducive to the coordinated development of cities. In order to further analyze the industrial structure of resource-based cities systematically and analyze the comprehensive level of resource-based cities from multi-dimensional perspective. This paper took 8 resource-based cities in Sichuan Province as the research object, and constructed the index system from two systems: industrial structure and ecological environment, then the shift-share analysis, entropy weight method and capacity coupling coefficient model were used to analyze their level of industrial structure, ecological environment and the coupling relationship respectively. According to the results of the study, it can be concluded that the main influencing factor in the development of industrial structure is the industrialmix effect, while the ecological level presents a decreasing level due to the lack of control of total industrial solid waste and energy consumption. The coupling degree between industrial structure and ecological environment in resource-based cities in Sichuan Province is relatively stable, and the coupling coordination degree also gradually tends to a stable state. In the subsequent development, the focus should be on the coal mining and dressing industry and the power, heat production and supply industry. Starting with the actual industrial structure of resource-based cities and specific indicators that affected the ecological environment, this paper hereby analyzed the development momentum and unified and coordinated development status of resource-based cities. The main purpose of this paper is providing some technical support for resource-based cities to improve their coordinated urban development, and giving policy suggestions for the coordinated development of resource-based cities.